The utility of outpatient commitment: Reduced-risks of victimization and crime perpetration - Segal, Steven P. (Eur Psychiatry, 2019)
BACKGROUND: Outpatient civil commitment (OCC) provisions, community treatment orders (CTOs) in Australia and Commonwealth nations, are part of mental health law worldwide. This study considers whether and by what means OCC provides statutorily required “needed-treatment” addressing two aspects of its legal mandate to protect the safety of self (exclusive of deliberate-self-harm) and others. METHOD: Over a 12.4-year period, records of hospitalized-psychiatric-patients, 11,424 with CTO-assignment and 16,161 without CTO-assignment were linked to police-records. Imminent-safety-threats included perpetrations and victimizations by homicides, rapes, assaults/abductions, and robberies. “Need for treatment” determinations were validated independently by Health of the Nations Scale (HoNOS) severity-score-profiles. Logistic regressions, with propensity-score-adjustment and control for 46 potential confounding-factors, were used to evaluate the association of CTO-assignment with occurrence-risk of perpetrations and victimizations. RESULTS: CTO-assignment was associated with reducedsafety-risk: 17% ininitial-perpetrations,11%in initial-victimizations, and 22% for repeat-perpetrations. Each ten-community-treatment-days in interaction with CTO-assignment was associated with a 3.4% reduced-perpetration-risk. CTO-initiated-re-hospitalization was associated with a 13% reduced-initial-perpetration-risk, a 17% reduced-initial-victimization-risk, and a 22% reduced-repeat-victimization-risk. All risk-estimates appear to be the unique contributions of the CTO, CTO-initiated-re-hospitalization, or the provision of ten-community-treatment-days—i.e. after accounting for the influence of prior crimes and victimizations, ethnic-bias, neighborhood disadvantage and other between-group differences in the analysis. CONCLUSIONS: CTO assignment’s association with reduced criminal-victimization and perpetration-risk, in conjunction with requiring participation in needed-treatment via re-hospitalization and community-service, adds support to the conclusion that OCC is to some extent fulfilling its legal objectives related to protecting safety of self (exclusive of deliberate-self-harm), and others.